Working Capital Determination in Indonesian Companies during the Covid-19 Pandemic - Krismonika Hidayat; Hersugondo Hersugondo (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2022)
This study aimed to know the effect of the Covid-19 pandemic on the performance of companies in Indonesia, to analyze the working capital determination in Indonesia companies, to analyze the effect of Probability in financial distress in moderating the working capital relationship in Indonesia companies, and to analyze the influence of variables in providing its effect on the company's working capital. The sample used in this study was 59 companies registered in Indonesia for the period 2017-2021 taken by purposive sample method. The analytical method used was a multiple linear regression model using Spss 25 software.  The results showed that companies that manage working capital through conservative policies were a financial strategy to ensure liquidity in fulfilling their obligations to creditors, firm age (company age), long-term debt, and sales growth has a positive effect on working capital. Thus, an older company can run the company by presenting a higher level of working capital which can generate profits and a better company reputation which allows the company to get credit more easily.